Modelo de reclutamiento y selección del talento humano por competencias para las medianas empresas del sector lácteo del cantón Latacunga - Álvarez Zurita, Gabriela Lisbeth (2017)
Currently the medium-sized dairy companies worry about human capital that will help in each part of the organizations, the following invetigation aims to recommend a model selection and recruitment of the human resource competency for medium-sized company enterprises of the dairy sector of Latacunga Canton. Taking into consideration the administration and economy line for human and social development, the reason why this research is developed, it is the ignorance of new processes of recruitment and selection of human talent, which does not possess a staff with the competencies required at the time of cover with whole requierd profile, these processes performed in a traditional way by such reason was a bibliographic research which allowed to deepen the level of knowledge about the models of recruitment and selection dictated by various authors. Selection competency is the most acceptable, It allows to assess, hablities, knowlegmentss and aptitudes from the coming candidates.